Border Security Governance in Transition: The Uneven Impact of Ibu Kota Negara on West and North Kalimantan Borderlands - Nia Norlyanti; Anak Agung Banyu Perwita; Rodon Pedrason (Darul Yasin Al Sys, 2026)
Indonesia’s decision to relocate its national capital to Ibu Kota Nusantara (IKN) represents a major reconfiguration of state space with significant implications for border governance and the enactment of sovereignty. Although previous studies have largely emphasized the urban and economic dimensions of the relocation, limited attention has been given to how the IKN project reshapes border security governance and why its effects vary across different frontier regions. Drawing on critical geopolitics, border studies, and the security–development nexus, this study compares two segments of the Kalimantan–Malaysia border: West Kalimantan, encompassing Entikong, Aruk, and Badau, and North Kalimantan, encompassing Sebatik and Nunukan, before and after the IKN decision. The study employed qualitative content and discourse analysis of official documents, with the state’s border security strategy and enactment of sovereignty serving as the units of analysis. The findings demonstrate that the uniform, Indonesia-centric geopolitical reframing associated with IKN is enacted unevenly across the frontier. West Kalimantan emerges as a relatively mature yet neglected corridor of border formalization, whereas North Kalimantan constitutes a geographically proximate but underdeveloped frontier undergoing active reterritorialization. This divergence reveals a spatially differentiated gap between the governance and operational management of border security. The study concludes that capital relocation should not be interpreted as a uniform state-building project, as its security and territorial effects are mediated by distinct historical, infrastructural, and geopolitical conditions across border regions. These findings contribute to critical geopolitical and border studies by demonstrating how national spatial restructuring produces differentiated forms of sovereignty and border security governance.